Fresno County Bar Association Annual Bar Banquet Held at TorNino's - Watkins, Howard::::::::: (1989)
Out-going Fresno County Bar Association President G. Dana French smiles as he receives the Fresno County Bar Association's appreciation gift of a Genesis 3 BBQ set